ANALISIS KEMAMPUAN MENULIS KARYA ILMIAH DI KALANGAN MAHASISWA - nagari, mutiara fahma (IKIP Siliwangi, 2020)
Writing in tertiary institutions requires requirements both in terms of language, content and writing techniques, because tertiary institutions as an institution that will produce intellectuals, carry out writing activities as an integrated part of the entire teaching and learning process. Having knowledge about the material to be written, related to the above statement, this study discusses the ability to write scientific papers for students who have completed the combined course of writing scientific papers. The purpose of this research is to: (1) measure how students 'ability to write paper scientific papers, (2) students' ability to develop content, (3) students 'ability to organize paper scientific papers, (4) students' ability to determine vocabulary and good terms and right, (5) ability to sort and use appropriate language. This research was carried out using the qualitative descriptive method of population in this study. All 2016 a2 students in the Indonesian language study program who had finished joining the alloy course wrote scientific papers, because the population was too much to take samples randomly from the class so that there were 15 samples to study. . The results of the study were obtained from the results of observations of several papers that have been done by students, (1) from the content aspect the ability to write papers students get the highest score = 30, while the lowest score is 18, and the average score = 25.30. (2) from the organizational organizing aspect to the paper made the highest score = 15, and the lowest score = 13, and the average score 12.10. (3) from the vocabulary aspect and the term ability of students to get the highest score = 15, while the lowest score = 12, and the average = 12.40. (4) from the aspect of language use in a paper made by a student the highest score = 15, and the lowest score = 10, and the average = 13.10. (5) from the spelling and technical aspects of writing scientific papers the students made the highest score = 7, while the lowest score = 6, and the average = 6.10.